Cost-effectiveness analysis of treating patients with ntrk-positive cancer with the histology-independent therapy entrectinib - Huygens, S; Vellekoop, H; Versteegh, M; Santi, I; Szilberhorn, L; Zelei, T; Nagy, B; Tsiachristas, A; Koleva-Kolarova, R; Wordsworth, S; Rutten-van Mölken, M (Elsevier, 2022)
Objectives This study tackles several challenges of evaluating histology-independent treatments using entrectinib as an example. Histology-independent treatments are provided based on genetic marker(s) of tumors, regardless of the tumor type. We evaluated the lifetime cost-effectiveness of testing all patients for NTRK fusions and treating the positive cases with entrectinib compared with no testing and standard of care (SoC) for all patients. Methods The health economic model consisted of a decision tree reflecting the NTRK testing phase followed by a microsimulation model reflecting treatment with either entrectinib or SoC. Efficacy of entrectinib was based on data from basket trials, whereas historical data from NTRK-negative patients were corrected for the prognostic value of NTRK fusions to model SoC. Results “Testing” (testing for NTRK fusions, with subsequent entrectinib treatment in NTRK-positive patients and SoC in NTRK-negative patients) had higher per-patient quality-adjusted life-years (QALYs) and costs than “No testing” (SoC for all patients), with a difference of 0.0043 and €732, respectively. This corresponded to an incremental cost-effectiveness ratio (ICER) of €169 957/QALY and, using a cost-effectiveness threshold of €80 000/QALY, an incremental net monetary benefit of −€388. When excluding the costs of genetic testing for NTRK fusions, the ICER was reduced to €36 290/QALY and the incremental net monetary benefit increased to €188. Conclusions When treatment requires the identification of a genetic marker, the associated costs and effects need to be accounted for. Because of the low prevalence of NTRK fusions, the number needed-to-test to identify patients eligible for entrectinib is large. Excluding the testing phase reduces the ICER substantially.